The Implementation of the Logico Maximo Game to Young EFL Learners' Vocabulary Learning - Putri, Ardelia Rana; Aisyah, Siti; Musyarofah, Lailatul; Prasetyo, Yudy (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
This study explores the use of the Logico Maximo game as an interactive medium to support vocabulary acquisition among young EFL learners at ILC English Course. Data was collected through student questionnaires, interviews with a fellow teacher and course manager, and classroom observation using a descriptive qualitative methodology. According to the results, Logico Maximo creates a more expanding, interesting, and enjoyable learning environment. The game's sensory and visual elements were well received by the students, encouraging active engagement and enhancing vocabulary memory. Nevertheless, the study also noted a varietyof difficulties, such as differing student comprehension levels, time management issues, and practical limitations in game implementation. Despite these issues, both the teacher and stakeholders viewed the game as an effective tool for enriching vocabulary learning. The results support previous research on the benefits of game-based learning in EFL contexts, particularly for early learners who thrive on multimodal and play-based instruction. It is suggested that future implementations include task differentiation and additional support mechanisms to accommodate learners with diverse needs.